A New Single Gene Differential Biomarker for Mycobacterium tuberculosis Complex and Non-tuberculosis Mycobacteria - Zhou, Lei; Ma, Cuidie; Xiao, Tongyang; Li, Machao; Liu, Haican; Zhao, Xiuqin; Wan, Kanglin; Wang, Ruibai (Frontiers in Microbiology, 2019)
Background: Tuberculosis (TB) and nontuberculous mycobacteriosis are serious threats to health worldwide. A simple non-sequencing method is needed for rapid diagnosis, especially in less experienced hospitals, but there is no specific biomarker commonly used for all mycobacteria. The ku gene of the prokaryotic error-prone non-homologous end joining system (NHEJ) has the potential to be a highly specific detection biomarker for mycobacteria. Methods: A total of 7294 mycobacterial genomes and 14 complete genomes of other families belonging to Corynebacteriales with Mycobacteriaceae were downloaded and analyzed for the existence and variation of the ku gene. Mycobacterium tuberculosis complex (MTBC) and non-tuberculosis mycobacteria (NTM)- specific primers were designed and the actual amplification and identification efficiencies were tested with 150 strains of 40 Mycobacterium species and ten kinds of common respiratory pathogenic bacteria. Results: The ku gene of the NHEJ system was ubiquitous in all genome sequenced Mycobacterium species and absent in other families of Corynebacteriales. On the one hand, as a single gene non-sequencing biomarker, its specific primers could effectively distinguish mycobacteria from other bacteria, MTBC from NTM, which would make the clinical detection of mycobacteria easy and have great clinical practical value. On the other hand, the sequence of ku gene can effectively distinguish NTM to species level with high resolution. Conclusion: The Ku protein existed before the differentiation of Mycobacterium species, which was an important protein involved in maintaining of the genome’s integrity and related to the special growth stage of mycobacteria. It was rare in prokaryotes. These features made it a highly special differential biomarker for Mycobacterium.